Incidencia del uso de los estilos de aprendizaje en la asignatura de matemática en el logro de aprendizajes significativos en los estudiantes del décimo año de educación general básica del colegio de bachillerato Hernán Gallardo Moscoso de la ciudad de Loja, periodo 2016 - 2017. Lineamientos alternativos - Quituisaca Castro, Jaime Fernando (2017)
The present research refers to the INCIDENCE OF THE USE OF LEARNING STYLES IN THE SUBJECT OF MATHEMATICS IN THE ACHIEVEMENT OF SIGNIFICANT LEARNING IN STUDENTS OF THE ELEVENTH YEAR OF BASIC GENERAL EDUCATION OF THE SCHOOL OF BACHILLERATO HERNÁN GALLARDO MOSCOSO DE LA CIUDAD DE LOJA, PERIOD 2016 - 2017. In which it was proposed as a general objective to determine the incidence of learning styles in the Mathematics subject, to achieve meaningful learning in the students of the tenth year of Basic General Education of the High School Hernán Gallardo Moscoso of the city Of Loja, period 2016 - 2017, this is a descriptiveexplanatory research because it allowed to describe and explain the incidence of learning styles in the achievement of meaningful learning, for the development of research was used as a survey instrument , This was done to students and teacher with the finali To gather the necessary and pertinent information, based on this one could conclude that learning styles in the area of Mathematics are the direct and fundamental means in the teaching-learning process because they provide the necessary resources and Direct students to learn and thus achieve meaningful learning